2013
DOI: 10.1177/0003319713508218
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related To Venous Ulceration

Abstract: The aim of the study was to determine the factors related to venous ulceration. Patients with venous ulceration (278 patients) were compared with 1401 patients in other categories of clinical classification of venous disease (clinical, etiologic, anatomic, and pathophysiological [CEAP]). Demographic, anthropometric, and clinical data were collected. Univariate and multivariate logistic regression analyses were used. According to multivariate analyses, risk factors for venous ulceration were age, male sex, pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 37 publications
(50 reference statements)
2
32
0
5
Order By: Relevance
“…Eventually, five studies, two case–control and three cross‐sectional studies, were included in the qualitative synthesis. Heterogeneity of the studies prevented us from doing a meta‐analysis.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Eventually, five studies, two case–control and three cross‐sectional studies, were included in the qualitative synthesis. Heterogeneity of the studies prevented us from doing a meta‐analysis.…”
Section: Resultsmentioning
confidence: 94%
“…In all studies, age and gender were investigated, matched for, or controlled for in VLU patients compared to CVD <C5 patients. In three studies, age was significantly higher in the VLU group compared to age in the CVD <C5 group . One study found no significant difference in age between the VLU group and CVD <C5 group.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Bizim çalışmamızda da literatür ile uyumlu olarak kadın hastalar çoğunluktaydı. Hastalarda VY şiddeti ve süresi arttıkça eşlik eden arteryel hipertansiyon, kalp yetmezliği, DM, PAH, kronik obstrüktif akciğer hastalığı, iskelet sistemi yada eklem hastalıklarının sıklığı da artmaktadır [16][17]. Trombositlerin endotel hasarı ve hemostazda çok önemli rolü mevcuttur, ayrıca aterotromboz gelişiminde de önemlidirler.…”
Section: Bulgularunclassified
“…4 Many studies have suggested a higher prevalence of VLU in women, 5 but this disparity decreased with age, 6,7 and in fact a more recent cross-sectional study suggested male gender carried a higher risk to develop VLU. 8 Nevertheless, the overall economic and social burden worldwide is huge.…”
Section: Introductionmentioning
confidence: 99%